Identifikasi Tanaman Obat Herbal Berbasis Citra - Mina Ismu Rahayu; Rahmat Jaenal; Muhamad Handy Risyandi (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
The Image-Based Herbal Plant Identification System or DETAMO is an application developed to assist the public in identifying medicinal plant species. The method involves teaching about herbal plants using image processing technology, employing Convolutional Neural Network (CNN) architecture. The acquired learning serves as the basis for mobile-based plant identification. Research findings demonstrate sufficient accuracy in recognizing various types of medicinal plants and provide alternative recipes for utilizing these herbal plants. The proposed system also manages variations in images caused by differences in lighting, position, and plant growth conditions.